PENGARUH PENYULUHAN KESEHATAN TERHADAP PENGETAHUAN DAN SIKAP KLIEN GOUT ARTHRITIS DI PUSKESMAS TAHUNA TIMUR KABUPATEN SANGIHE - Kurniawati, Eni; Kaawoan, Adeleida; Onibala, Franly (Universitas Sam Ratulangi, 2014)
Abstract: Gout Arthritis is a type of rheumatic diseases associated with impaired acid kinetic namely hyperuricemia. Hyperuricemia is a uric acid levels in the blood above normal, according to data from the District Health Center East Tahuna. Regency of Sangihe mentioned in the period January 2014 to March 2014 there were 143 patients with Gout Arthritis. The purpose of this study was to determine the effect of health education on knowledge and attitude of Gout Arthritis clients in health center East Tahuna. The research method used was a pre-experimental design with